The impact of physician communication skills on glycemic control in patients with diabetes mellitus - Alotaibi, Faisal Nahes; Aburisheh, Khaled Hani; Alrasheed, Abdulelah Ibrahim; Alazmi, Alwaleed Khalaf; Alamri, Khalid Dhaifallah; Alotaibi, Nawaf Nahes; Alotaibi, Anas Nahes; Alhoqail, Abdulaziz Abdulkarem (Frontiers in Communication, 2024)
The purpose of the study was to evaluate the impact of physicians' communication skills on glycemic control in type I and II diabetes patients. Method: This cross-sectional study was conducted at the diabetic center at King Saud University Medical City, Riyadh, Saudi Arabia. The Arabic version of the communication assessment tool was used to evaluate the patient's perception of the physicians' communication skills. Results: A total of 348 patients were invited to participate in the study in which 332 filled the questionnaire completely and hence participation rate was 95.4%. The average age of the patients was 44.2(±19.7) years with an almost equal gender ratio. The percentage of excellent ratings for most of the questions was varying between 70% to 80%. The overall percentage of excellent ratings was 75.3%. Glycated hemoglobin and other metabolic features except for diastolic blood pressure did not have any significant association with the overall mean communication assessment tool score and the percentage of excellent rating. Conclusion: Study findings provided high patient satisfaction with their physicians' communication skills. However, diabetes and metabolic control were not affected by this satisfaction. Hence, improvement in the communication skills of the physicians is recommended.